The influence of social media viral status on the acceleration of criminal law processes in indonesia - Gema Goeyardi (INFOKUM, 2024)
Social media viral status refers to statuses, pictures, photos, videos, and all other information that spreads quickly and widely, so that viral information is widely known by the wider community, and has become a topic of discussion by many netizens or netizens in cyberspace. The purpose of this study is to determine the effect of social media viral status on accelerating the criminal justice process in Indonesia, as well as solutions for the community regarding the viral social media status. The method in this study uses qualitative analysis methods. The data collection technique in this study was for primary data by means of documentary studies and interviews and for secondary data by studies of primary, secondary and tertiary legal materials. The results in this study state that there is an influence of social media viral status on the acceleration of the criminal justice process in Indonesia. As well as solutions for law enforcement agencies such as the police in fixing the public complaint system, namely Improving the Complaint Acceptance System, Training and awareness for officers, Building an Evaluation and Monitoring System, Strengthening collaboration with social media, Increasing Transparency and Public Communication, and internal evaluation and system improvement.